2011
DOI: 10.1002/eji.201141748
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Tfh‐like cells during chronic Salmonella exposure mediates the generation of autoimmune hypergammaglobulinemia in MyD88‐deficient mice

Abstract: The role of TLR signaling in linking the innate and adaptive immune systems has been a controversial issue that remains to be solved. Here, we determined whether MyD88-dependent TLR signals are required for the generation of B-cell responses during chronic Salmonella infection. Oral administration of recombinant attenuated Salmonella enterica serovar Typhimurium vaccine (RASV) strain in MyD88 À/À mice resulted in chronic infection. Infection was accompanied by enlarged germinal centers and hypergammaglobulinem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Blockage of PD1 expression or delivery of Fc-fused IL-7 can restore Tfh cell function and enhance the secretion of Abs from B cells in response to influenza virus challenge, suggesting a critical role of Tfh cells in humoral immunity [72-75]. Similar results were found in bacterial infection, as which blockage of PD1 can reverse chronic salmonella infection induced high levels of Abs via its inhibitory effect on Tfh cells function [76]. In addition, Tfh cells dysfunction decreased the secretion of IgA plasma cells in the gut of PD1 deficient mice [77, 78], subsequently destroying the integrity of the intestinal barrier and increasing the translocation of microbial products from gut, which has been implicated as an important mechanism for B cells dysfunction in HIV infected patients [79-81].…”
Section: Introductionmentioning
confidence: 75%
“…Blockage of PD1 expression or delivery of Fc-fused IL-7 can restore Tfh cell function and enhance the secretion of Abs from B cells in response to influenza virus challenge, suggesting a critical role of Tfh cells in humoral immunity [72-75]. Similar results were found in bacterial infection, as which blockage of PD1 can reverse chronic salmonella infection induced high levels of Abs via its inhibitory effect on Tfh cells function [76]. In addition, Tfh cells dysfunction decreased the secretion of IgA plasma cells in the gut of PD1 deficient mice [77, 78], subsequently destroying the integrity of the intestinal barrier and increasing the translocation of microbial products from gut, which has been implicated as an important mechanism for B cells dysfunction in HIV infected patients [79-81].…”
Section: Introductionmentioning
confidence: 75%
“…Passive transfer experiments indicated that antibodies, IgM and IgG, induced as a result of parasite induced polyclonal B cell activation promoted parasite growth. While Tfh cells have been reported as triggering hypergammaglobulinemia during chronic Salmonella infection (Ko et al, 2011) whether they can do this early in visceral leishmaniasis remains to be determined.…”
Section: Follicular Helper Cd4+ T Cells and Their Potential Role In Lmentioning
confidence: 99%
“…These observations suggest that the overrepresentation of T FH -like cells in chronic bacterial infection elicits autoimmune pathologies in a PD-1-and ICOS-dependent fashion. 38 Aberrant production of T FH cell-associated cytokines, particularly IL-21 has been shown to be critical for the development of autoimmunity in lupus-prone mice. IL-21 is mainly produced by T FH cells and appears to be crucial for T FH -cell differentiation and GC reactions.…”
Section: T Fh Cells In Murine Models Of Autoimmune Diseasesmentioning
confidence: 99%